Концепт БОГОРОДИЦА в украинской и польской языковых картинах мира - Татьяна [Tat′iana] Николаевна [Nikolaevna] Сукаленко [Sukalenko]; Наталия [Nataliia] Богдановна [Bogdanovna] Ладыняк [Ladyniak] (Studia z Filologii Polskiej i Słowiańskiej, 2022)
The Concept MOTHER OF GOD in the Ukrainian and Polish Linguistic Worldviews